Neutrophile-lymphocyte ratio and outcome in takotsubo syndrome. (3rd October 2022) - Zweiker, D; Pogran, E; Gargiulo, L; El-Razek, A; Vosko, I; Rechberger, S; Bugger, H; Christ, G; Bonderman, D; Kunschitz, E; Zirlik, A; Bauer, A; et al.
Abstract: Introduction: Takotsubo syndrome (TTS) is an important form of acute heart failure with significant risk of acute complications and death. In this analysis we sought to identify predictors for in-hospital clinical outcome in TTS patients by concentrating on routine laboratory parameters at admission. Methods: In this analysis from the Austrian national TTS registry, univariable and multivariable analyses were performed to identify significant predictors for severe in-hospital complications requiring immediate invasive treatment or leading to irreversible damage, such as cardiogenic shock, intubation, stroke, arrhythmias and death. Furthermore, the influence of identified predictors with long-term survival was evaluated. Results: A total of 338 patients (median age 72 years, 86.9% female) from 6 centres were included. Severe in-hospital complications occurred in 14.5% of patients, including cardiogenic shock (9.8%), death (3.3%) and intubation (1.2%), respectively. Patients with complications during the hospital stay had more prevalent chronic kidney disease (CKD), were less often previous smokers and TTS was less often preceded by an emotional trigger. C-reactive protein and neutrophile lymphocyte ratio (NLR) was higher in patients with complications, and midventricular ballooning and reduced left ventricular ejection fraction (LVEF) were more prevalent. In multivariable analysis, high NLR (OR 1.04 [95% CI 1.02–1.07], p=0.009) and low LVEF (OR 0.92 [0.90–0.95] per %, p<0.001) remained significant predictors for severe in-hospital complications. Both the highest NLR tercile and the lowest LVEF tercile were associated with significantly reduced 5-year survival. Discussion: Low LVEF and high NLR at admission were independently associated with increased in-hospital complications and reduced long-term survival in TTS patients. NLR is a new easy-to-measure tool to predict worse short and long-term outcome after TTS. Funding Acknowledgement: Type of funding sources: None.